THE INFLUENCE OF STUDENTS’ SELF EFFICACY ON INTEREST TO BE A TEACHER - Mariska, Shinta Sofi; Suharni; Yendra (JEE (Journal of English Education), 2023)
This study aimed to determine the influence of student self-efficacy on interest in becoming a teacher. This study is a quantitative study used correlation method with regression analysis. In this study, researchers chose students of the English language education study program at University of PGRI Sumatera Barat with a sample of 69 students selected using the total sampling technique. This study used a questionnaire as a study instrument. The results showed that there was a strong relationship between student self-efficacy and interest in becoming a teacher (rxy = 0.721). The influence of student self-efficacy on interest to be a teacher is 51.9%. From the t test the results obtained tcount (>) ttable = 8.509 (>) 1.996. Then hypothesis is accepted and the null hypothesis is rejected. It can be concluded that there is a significant influence of student self-efficacy on interest in becoming a teacher at University PGRI Sumatera Barat. This study aimed to determine the influence of student self-efficacy on interest in becoming a teacher. This study is a quantitative study used correlation method with regression analysis. In this study, researchers chose students of the English language education study program at Universitas PGRI Sumatera Barat with a sample of 69 students selected using the total sampling technique. This study used a questionnaire as a study instrument. The results showed that there was a strong relationship between student self-efficacy and interest in becoming a teacher (rxy = 0.721). The influence of student self-efficacy on interest to be a teacher is 51.9%. From the t test the results obtained tcount (>) ttable = 8.509 (>) 1.996. Then hypothesis is accepted and the null hypothesis is rejected. It can be concluded that there is a significant influence of student self-efficacy on interest in becoming a teacher at Universitas PGRI Sumatera Barat.